Surface wave plasma source for broad-beam ion and electron production - Azarenkov, N.A.; Bizyukov, A.A.; Gapon, A.V.; Olefir, V.P.; Kashaba, A.Y.; Sereda, K.N.; Tarasov, I.K. (Вопросы атомной науки и техники, 2004)
The new type of multipurpose plasma source based on the surface wave sustained discharge is presented. The plasma in the source is generated by the RF surface wave discharge excited by the antenna system placed inside a cylindrical metal chamber. Charged particle acceleration is carried out by a quasi-stationary electric field due to DC voltage applied to the cylindrical electrode mounted inside the chamber. The source can be used for production and acceleration of ion as well as electron beams. The source has stable low-pressure operation in the range of applied RF power from 50 to 1000 W and produce ion beam having a density up to 0.3 mA/cm2 in the energy range from 50 to 200 eV and 3% homogeneity on the 300 mm diameter. Представлено новий тип багатоцільового плазмового джерела на основі розряду на поверхневих хвилях. Плазма у джерелі створюється ВЧ-розрядом на поверхневих хвилях, що збуджується за допомогою антенної системи, яка міститься всередині циліндричної камери. Прискорення заряджених частинок здійснюється квазістаціонарним електричним полем завдяки сталій напрузі, яка прикладена до циліндричного електроду, що міститься у камері. Джерело можна використовувати для отримання та прискорення як іонних, так і електронних пучків. Джерело стабільно працює при низькому тиску в діапазоні прикладеної ВЧ потужності від 50 до 1000 Вт і генерує іонний пучок з густиною до 0,3 мА/см2 в діапазоні енергій (50…200) еВ при 3% однорідності на діаметрі 300 мм. Представлен новый тип многоцелевого плазменного источника на основе разряда на поверхностных волнах. Плазма в источнике генерируется ВЧ-разрядом на поверхностных волнах, возбуждаемым с помощью антенной системы, расположенной внутри цилиндрической камеры. Ускорение заряженных частиц осуществляется квазистационарным электрическим полем за счет постоянного напряжения, приложенного к цилиндрическому электроду, расположенному внутри камеры. Источник можно использовать для получения и ускорения как ионных, так и электронных пучков. Источник стабильно работает при низком давлении в диапазоне приложенной ВЧ мощности от 50 до 1000 Вт и генерирует ионный пучок с плотностью до 0,3 мА/см2 в диапазоне энергий (50…200) эВ при 3% однородности на диаметре 300 мм.